Semantic Analysis On Harris J’s Song Lyrics As Related To The Holy Qur’an Values - Anisa Rizki; Alfian Alfian; Ulfatmi Azlan (English Literature Department, Adab and Humanities Faculty, 2021)
This research discussed the analysis of lexical meaning and contextual meaning on Harris J’s song lyrics that have related values in the Quran. The purpose of this study to describe the kinds of class of words, the lexical and contextual meaning and the Qur’an values which are presented to Harris J's song lyrics in SALAM Album. This research employed qualitative research and descriptive method because it was used to describe the contextual meaning found in song lyrics of Harris J. The writer used the contextual meaning theory by Mansoer Pateda to conduct this research. The data were taken from first album SALAM by Harris J, five songs they are Salam Alaikum, Rasool'Allah, I Promise, The One and You Are My Life. The first results showed that there are seven kinds of class of words, consisting of; noun, noun phrase, verb, verb phrase, adjective, adjective phrase and adverb. Also the writer found that noun phrase and verb are more dominantly found in song lyrics in the Album SALAM. Second, the contextual meaning in lyrics of the song had the meaning according to the context, but not all people know that contexts. From five songs by Harris J, there were fifteen words, phrases, or sentences found as the context. Third, there are twelve surah and fourteen verses in the Qur'an that the values of the verse relate to the song lyrics from Salam Album.